The roles of social status information in irony comprehension: An eye-tracking study - Wu, Zixuan; Wang, Yuxia (Frontiers in Psychology, 2022)
The literature on irony processing mainly focused on contextual effect, leaving other factors (such as social factors) untouched. The current study investigated how social status information affected the online comprehension of irony. As irony might be more damaging when a speaker uses it to a superordinate than the other way around, it is assumed that greater processing efforts would be observed in the former case. Using an eye-movement sentence reading paradigm, we recruited 36 native Mandarin speakers and examined the role of social status information and literality (i.e., literal and irony) in their irony interpretation. Our results showed ironic statements were more effortful to process than literal ones, reporting an early and consistent effect on the target regions. The social status effect followed the literality effect, with more difficulty in processing ironic statements that targeted the superordinate than the subordinate; such an effect of social status was missing with literal statements. Besides, an individual’s social skill appeared to affect the perception of status information in ironic statements, as the socially skillful readers needed more time than the socially unskillful to process irony targeting a subordinate in the second half of the experiment in the critical region. Our study suggests that irony processing might be further discussed in terms of the relative predictability of linguistic, social, and individual variabilities.